The good, the bad, the authentic. An evaluation of concepts, experiences, and considered values of authenticity of place in the context of the post-industrial city. - Wesener, Andreas (Königshausen & Neumann, 2014)
In Reaktion auf einen immer stärker wahrgenommenen globalen Wettbewerb zwischen Städten, versuchen diese auf der Grundlage von Alleinstellungsmerkmalen Investoren, Unternehmen, Facharbeiter und Touristen anzuziehen. Die Authentizität ist als weicher Standortfaktor mit weitreichenden Potenzialen für Stadtentwicklung und städtische Regeneration konzeptualisiert worden. Ziel dieser Arbeit ist es, Konzepte, Erfahrung und Erleben sowie Wertvorstellungen von Authentizität im Zusammenhang mit Orten herauszuarbeiten.

in response to perceived increased global competition, cities try to exhibit distinctive features to attract investors, businesses, skilled workers, and tourists. Authenticity of place has been considered as an influential soft location factor able to enhance urban (re-)development and regeneration. However, despite its suggested significance, authenticity of place has rarely been subject of systematic theoretical and empirical research. The book addresses this apparent research gap. It investigates how authenticity is contextually intertwined with concepts, experiences, constituting elements, meanings and values of place. With the help of a comprehensive theoretical discussion and a case study - the Jewellery Quarter in Birmingham, UK - the author analyses how concepts of authenticity have been conveyed to places and how meanings correspond to particular identity constructions. Two key notions of authenticity of place are identified: First, 'empirical authenticity', second, 'experiential authenticity'.
Keywords: Standort; Standortfaktor; Stadtplanung; Stadtentwicklung; Stadtsoziologie; Stadtgestalt; Attraktivität; Räumliche Identität; Stadtmarketing; Stadtimage; Weicher Standortfaktor